1995
DOI: 10.1074/jbc.270.36.21151
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction between CD45 and CD45-AP

Abstract: CD45, a leukocyte-specific transmembrane protein tyrosine phosphatase, is required for critical signal transduction pathways in immune responses. To elucidate the molecular interactions of CD45 with other proteins involved in CD45-mediated signal transduction pathways, we have recently cloned a 30-kDa phosphorylated protein, CD45-AP, which specifically associates with CD45. Binding analysis employing several deleted or chimeric forms of CD45-AP and CD45 demonstrated that the potential transmembrane segment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
3
27
0
1
Order By: Relevance
“…Even though the levels of CD45-AP were reduced in CD45-negative YAC-1 cells, the inability of the remaining CD45-AP (20% of control) to coimmunoprecipitate with TCR would be consistent with the notion that CD45 was bridging the interaction between these two molecules. This idea is also in keeping with the previous observations that CD45 can interact with the TCR complex by way of its extracellular domain (20,50), whereas it associates with CD45-AP via its transmembrane domain (25,28,29,51).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Even though the levels of CD45-AP were reduced in CD45-negative YAC-1 cells, the inability of the remaining CD45-AP (20% of control) to coimmunoprecipitate with TCR would be consistent with the notion that CD45 was bridging the interaction between these two molecules. This idea is also in keeping with the previous observations that CD45 can interact with the TCR complex by way of its extracellular domain (20,50), whereas it associates with CD45-AP via its transmembrane domain (25,28,29,51).…”
Section: Discussionsupporting
confidence: 73%
“…CD45-AP was discovered on the basis of its capacity to associate with CD45, via its transmembrane domain (25,28,29,51). In addition to confirming this association, our results revealed that CD45-AP could be coimmunoprecipitated with the antigen receptor complex in Brij-97 lysates of T-cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…2 Since p56 lck has not been co-precipitated in the absence of the 30-kDa protein (CD45AP or LPAP), it is not known whether p56 lck can directly associate with CD45 in T cells. In contrast, p30 has been shown to co-precipitate with CD45 in the absence of p56 lck (20), and recently, the transmembrane region of CD45 has been shown to be required for the association of p30 (42). However, as only a small percentage of p56 lck is co-precipitated with CD45, 2 the physiological significance of this association remains to be established.…”
Section: Fig 6 Binding Of Recombinant Gst Sh2 Domain Fusion Proteinmentioning
confidence: 93%
“…For example, the extracellular domain of CD45, primarily CD45R0, has been reported to associate with CD4, which in turn binds Lck (41,42). Although the transmembrane region of CD45 is not required for its association with Lck, it does mediate an interaction with CD45AP (43), which also binds to Lck (44). Although CD45RABC-D2 can associate with Lck in the absence of CD45, CD45RABC-D2 may also bind to CD45 because a small amount co-immunoprecipitated with endogenous CD45 (data not shown).…”
Section: Discussionmentioning
confidence: 99%